1999
DOI: 10.1074/jbc.274.44.31127
|View full text |Cite
|
Sign up to set email alerts
|

Sensing of Ionizing Radiation-induced DNA Damage by ATM through Interaction with Histone Deacetylase

Abstract: The ATM gene is mutated in individuals with ataxia telangiectasia, a human genetic disease characterized by extreme sensitivity to radiation. The ATM protein acts as a sensor of radiation-induced cellular damage and contributes to cell cycle regulation, signal transduction, and DNA repair; however, the mechanisms underlying these functions of ATM remain largely unknown. Binding and immunoprecipitation assays have now shown that ATM interacts with the histone deacetylase HDAC1 both in vitro and in vivo, and tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
66
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 102 publications
(71 citation statements)
references
References 30 publications
(29 reference statements)
4
66
0
Order By: Relevance
“…Importantly, the findings indicated that ionizing radiation enhances ATM-associated HDAC activity suggesting that HDACs may have a critical role in ATM signaling in response to DNA damage (Kim GD et al, 1999). The fact that this study demonstrated that TSA inhibits this ATM-associated HDAC activity, provides an insight into a possible mechanism by which HDAC inhibitors may enhance the radiation sensitivity of cells (Kim GD et al, 1999).…”
Section: Mechanisms Of Hdac Inhibitor-mediated Enhanced Radiation Senmentioning
confidence: 70%
See 1 more Smart Citation
“…Importantly, the findings indicated that ionizing radiation enhances ATM-associated HDAC activity suggesting that HDACs may have a critical role in ATM signaling in response to DNA damage (Kim GD et al, 1999). The fact that this study demonstrated that TSA inhibits this ATM-associated HDAC activity, provides an insight into a possible mechanism by which HDAC inhibitors may enhance the radiation sensitivity of cells (Kim GD et al, 1999).…”
Section: Mechanisms Of Hdac Inhibitor-mediated Enhanced Radiation Senmentioning
confidence: 70%
“…It has been shown using human fibroblasts that ATM interacts with HDAC1 both in vitro and in vivo (Kim GD et al, 1999;Ju and Muller, 2003). Importantly, the findings indicated that ionizing radiation enhances ATM-associated HDAC activity suggesting that HDACs may have a critical role in ATM signaling in response to DNA damage (Kim GD et al, 1999).…”
Section: Mechanisms Of Hdac Inhibitor-mediated Enhanced Radiation Senmentioning
confidence: 99%
“…Linkage between p21 and radiation-induced tumorigenesis Z Li et al HDAC1 is a major deacetylase whose genetic deletion causes a significant reduction in total HDAC activity (Zupkovitz et al, 2006), and its involvement in cancer has been established (Lin et al, 1998). In addition, HDAC1 has been implicated in ATM-mediated sensing of IR-induced DNA damage (Kim et al, 1999), implying the potential crosstalk between FATS and ATM. Although we cannot rule out the possibility that the interaction between FATS and HDAC1 may also abolish HDAC1-mediated repression of p21 transcription, which acts through a general transcription factor Sp1 (Lagger et al, 2002;Lagger et al, 2003), such effect on FATS-mediated induction of p21 is negligible, as FATS did not affect the expression of p27, whose expression is also mediated by Sp1 (Wei et al, 2003;Cen et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…ATM plays critical roles in radiationinduced responses (Kastan et al, 2001;Kurz and Lees-Miller, 2004), and has been identified as a potential target for novel radiosensitizers (Sarkaria andEshleman, 2001, Ahmed andLi 2007). For example, small molecule inhibitors of ATM or downstream signaling molecules (Kim et al, 1999;Jung and Dritschilo, 2001) may offer a strategy to sensitize tumors to the lethal effects of ionizing radiation while sparing normal tissues.…”
Section: Introductionmentioning
confidence: 99%